Electrochemical Sensing of Nitrite Ions Using Modified Electrode by Poly 1,8-Diaminonaphthalene/Functionalized Multi-Walled Carbon Nanotubes - Salhi, Ouissal; Ez-zine, Tarik; Oularbi, Larbi; El Rhazi, Mama (Frontiers in Chemistry, 2022)
A novel electrochemical sensor based on conducting polymer and multi-walled carbon nanotubes was reported for the detection of nitrite ions (NO2−). The hybrid material poly 1,8-Diaminonaphthalene (poly 1,8-DAN)/functionalized multi-walled carbon nanotubes (f-MWCNT) was prepared by using a simple electrochemical approach which is based on the deposition of functionalized multi-walled carbon nanotubes (f-MWCNT) on the surface of the electrode followed by the electropolymerization of 1,8-DAN using cyclic voltammetry. The morphology and the electro-catalytic properties of the obtained electrodes were investigated with Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Cyclic Voltammetry (CV), and Electrochemical Impedance Spectroscopy (EIS) showing an improvement of the electronic transfer due to the synergic effect between the proprieties of poly 1,8-DAN and f-MWCNT. Under the optimum experimental conditions, the poly 1,8-DAN/f-MWCNT/CPE exhibited excellent electro-catalytic activity towards nitrite detection. The nitrite anodic peak potential decreased by 210 mV compared to the bare carbon paste electrode. The calibration plot of nitrite detection was linear in the range of concentration from 300 to 6500 nM with a low detection limit of 75 nM.